Tingkat Pengetahuan Mahasiswa dalam Membedakan Tulisan Jurnalistik - Dewi Anggraini (Jurnal Bahasa dan Sastra, 2021)
Journalism knowledge with all forms of writing is the product offered to students of Program Studi Pendidikan Bahasa Indonesia, Faculty of Languages And Arts, Universitas Negeri Padang through journalism package courses as predominant skills besides language, literature, and teaching skills. Based on this condition, this study is intended to measure the degree of student knowledge in distinguishing journalistic writing. This research is quantitative research with descriptive methods. Quantitative analysis is designed to measure and describe the level of student knowledge. The population of this study was 453 students of the Pendidikan Bahasa Indonesia study program. Based on the provisions of the research variables, students who had passed the introductory journalism, editorial, and news photography courses were students in 2014 who were used as the research population as many as 105 people. The research sample was taken with Taro Yamane's formula with a precision level of 10% to 51 students. Based on the results of the data analysis, it was found that the student's knowledge of distinguishing journalistic writing was in the range of 79.90%. This result shows that students' knowledge in determining the variety of journalistic writing is in the 'outstanding' criteria.